PENGUATAN LITERASI BACA TULIS DAN DIGITAL MELALUI PELATIHAN JURNALISME SASTRAWI DAN STORYTELLING - Mubarok, Muhamad Husni (Community Services and Social Work Bulletin, 2022)
After Covid 19, Indonesian students’ literacy rates have been slowly and steadily declining. The school needs to reorganize literacy creatively despite of limited face-to-face learning. Workshop of literary journalism and storytelling aimed to improve students’ literacy rates.   This workshop is a part of Bhayangkara University community service.  The implementation of this training is converted into five stages: introduction of journalism and digital media, SPOK patterning, writing narrative, and transforming article into digital.  The methods used PPP, inquiry, and Project Based Learning. Findings showed that students were able to use digital devices and creating descriptive text. Unfortunately, they have limited in vocabularies and figure of speech. They also lack of creating systematic paragraphs. After this training, students' views of literacy were increased positively, and their writing skills developed. However, this training can help students improve their think critically and strengthen students' literacy. This skill is a manifestation that can be developed into content writing and copywriting. Currently, the Indonesian industrial world really needs experts in this field. This skill is a great potential and timeless even though the digitalization is increasing.